The evaluation of cytotoxicity and cytokine IL-6 production of root canal sealers with and without the incorporation of simvastatin: an invitro study - Apoorva Sharma; Kavitha Sanjeev; Vinola M. J. Selvanathan; Mahalaxmi Sekar; Nikhil Harikrishnan (BMC, 2022)
Abstract Background Freshly mixed root canal sealers when proximate the periapical tissues, trigger varying degrees of cytotoxicity/inflammatory reactions. Simvastatin, a class of the drug statin, is a widely used cholesterol-lowering agent with additional anti-inflammatory activities. This study assessed the effects of simvastatin on cytotoxicity and the release of IL-6 (Interleukin-6) production when incorporated in zinc oxide eugenol and methacrylate resin-based sealers. Methods Experimental groups consisted of conventional zinc oxide eugenol and methacrylate based-EndoREZ sealers (ZE & ER respectively) and 0.5 mg/mL simvastatin incorporated sealers (ZES & ERS). L929 mouse fibroblast cells were exposed to freshly mixed experimental sealers and evaluated for cytotoxicity (MTT assay) and inflammation levels (inflammatory marker IL-6 for ELISA) at various time intervals (0h, 24h and 7th day). The values were compared to the cell control (CC; L929 cells alone) and solvent control (SC; L929 cells + DMSO) groups. All the experiments were conducted in triplicates and subjected to statistical analysis using IBM SPSS Statistics software. Non parametric tests were conducted using Kruskal-Wallis and Friedman tests for inter-group and intra-group comparisons respectively. Pairwise comparison was conducted by post hoc Dunn test followed by Bonferroni correction. P values < 0.05 were considered statistically significant. Results All the experimental groups (ZE, ER, ZES, ERS) exhibited varying degree of cytotoxicity and IL-6 expression compared to the control groups CC and SC. The cell viability for ZE and ER decreased on day 7 as compared to 24 h. ZES and ERS had higher viable cells (75.93% & 79.90%) compared to ZE and ER (54.39% & 57.84%) at all time periods. Increased expression of IL-6 was observed in ZE & ER (25.49 pg/mL & 23.14 pg/mL) when compared to simvastatin incorporated ZE & ER (ZES-12.70 pg/mL & ERS-14.68 pg/mL) at all time periods. Highest level of cytotoxicity and inflammation was observed in ZE compared to all the other groups on day 7. Conclusions Addition of 0.5 mg/mL of simvastatin to the sealers (ZES and ERS) decreased the cytotoxicity in the freshly mixed state and reduces their inflammatory effect.